A simple epidemic model of COVID-19 and its application to Ukrainian, Indonesian, and the global data - Serhii O. Soloviov; Mohamad S. Hakim; Iryna V. Dzyublyk; Serhii H. Ubohov; Ozar P. Mintser; Viktor V. Trokhymchuk (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
At the beginning of 2020, one of the most significant health problems for humanity is the pandemic of coronavirus disease 2019 (COVID-19). Here, we identify features and develop simple epidemic model of COVID-19 on the basis of available epidemiological data and existing trends worldwide. Modeling of COVID-19 epidemic process was based on a classic model. A key parameter of the model, i.e. transmission parameter of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was determined numerically with the use of available epidemiological daily reports of COVID-19 from 17 April to 23 May 2020. Numerical determination of transmission parameter of SARS-CoV-2 according to the absolute number of COVID-19 cases in Ukraine, Indonesia and worldwide data showed its global tendency to decrease over time. Approximation of the obtained numerical values of the transmission parameter of SARS-CoV-2 was carried out using the exponential function. The results of prognostic modeling showed that by the end of summer 2020, above 30 thousand COVID-19 cases are expected in Ukraine, 100 thousand COVID-19 cases in Indonesia, and 12 million COVID-19 cases worldwide. Thus, predicting the possible consequences of the implementation of various health care control programs COVID-19 involves a comprehensive study of the epidemic process of the disease as a whole and for certain periods of time with the subsequent construction of an adequate prediction model.